students' spoken english self-efficiency and teachers' interpersonal relations in akinyele local government area of oyo state. (2024)
The study explores the correlatoin between students' spoken english self-efficacy and teachers students interpersonal relationship in eight public schools within akinyele local government area. Employind a descriptive survey research design, it sample 400 senior secondary students from the selected school. Quantitative data were collected using selfdesigned scales: the Assessment of Teacher Interpersonal Relationship Scales(SATIRS) and |Spoken English Self-Efficacy Scale(SESS). Findinds indicate teachers generally maintain positive interpersonal relationships .